The Effect of Service Quality and Product Diversity on Customer Loyalty - Jefri, J.; Junaeda, J.; Suharlina, S. (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to determine the effect of Service Quality and Product Diversity on Customer Loyalty at TPC Raja Wallpaper in Mamuju Regency. The research method employed is quantitative, using primary data collected through questionnaires. The respondents in this study were all customers who made purchases at TPC Raja Wallpaper in Mamuju Regency. The sampling technique used was accidental sampling, with a sample size of 30 respondents. The analysis in this study utilizes multiple linear regression, validity testing, reliability testing, t-tests, and F-tests. The results indicate that both Service Quality and Product Diversity have a positive and significant partial effect on Customer Loyalty at TPC Raja Wallpaper in Mamuju Regency. Additionally, Service Quality and Product Diversity simultaneously significantly impact Customer Loyalty at TPC Raja Wallpaper in Mamuju Regency.